Development of Digital-Based Marketing Methods (Meta Ads) to Increase MSME Sales - Andhyka; Fathul Huda; Rahmat Yanuary; Jenita Frisilia; Kadek Bramdhika Ada (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The growth of MSMEs in developing areas, especially Palu City, continues to increase and some have failed so that they have to close their businesses. This failure can be caused by several factors, including limited budget for marketing, making it difficult to compete with large companies in terms of promotion and advertising. The difficulty in gaining sufficient visibility in a crowded and competitive market is often a factor in MSMEs sinking among larger and better-known competitors, making it difficult to reach and attract the attention of the right target market. Another factor is due to the lack of knowledge of MSME actors about modern marketing skills, such as the use of social media platforms and other digital marketing tools. This study aims to explore the effect of using meta ads on increasing sales of Micro, Small, and Medium Enterprises (MSMEs) in Palu City, so that they can have the right target market. This study will use a mixed method approach by combining quantitative and qualitative design methods with a sample size of 30 samples divided into two groups using ads marketing and conventional marketing. Bivariate data analysis using paired t-test showed that marketing through Meta Ads has a significant positive effect on the income of MSME actors compared to conventional marketing. Most respondents have proven that advertising is needed to attract consumers and that the use of social media, especially Meta Ads.